Don Juan Hernández López: Jurisconsulto, político y orador elocuente - Hernández López, Juan; Todd, Roberto H. (My University, 1943)
Datos de la vida de Don Juan Hernández López.
Keywords: Partido Liberal Puertorriqueño; Hernández López, Juan; Partido Autonomista Puertorriqueño